The effect of soccer match induced fatigue on neuromuscular performance - Zemkova, E.; Hamar, D. (Kinesiology, 2009)
The study evaluates the effect of soccer match induced fatigue on the neuromuscular performance. Prior to, during the break period between the 1st and 2nd part of the game and after the game, parameters of agility, explosive power of lower limbs, static and dynamic balance, speed of step initiation and the soccer kick were evaluated in a group of 10 soccer players. Reaction time in the agility test was measured using the FiTRO Agility Check. The task of the subject was to touch, as fast as possible, with either the left or right lower limb one of the four mattresses located in the four corners inside of a square (80 cm and 1.5 m, respectively) in accordance with the location of stimulus in one of the corners of the screen. Heights of squat jump (SJ) and countermovement jump (CMJ) were calculated from the flight time registered by the FiTRO Jumper. The same method was applied to measure contact time during a drop jump from a height of 45 cm. Postural stability was evaluated under both the static and dynamic conditions (wobble board) with the eyes open (EO) and eyes closed (EC). Velocity of the centre of pressure (COP) was registered at 100 Hz by means of the posturography system FiTRO Sway check based on a dynamometric platform. Speed of step initiation and the soccer kick were measured using the FiTRO Dyne. Results showed that after the first 45 minutes of a soccer match only dynamic balance with EC was impaired and the drop jump ground contact time increased. Its further increase was observed after the second part of the match. Along with it also the dynamic balance with EO and the agility performance in the test on a shorter (80 cm) distance between mats was affected. On the other hand, there were no pre-post match differences in the agility performance in the test on a longer (1.5 m) distance between mats, height of SJ and CMJ, speed of step initiation and soccer kick, and static balance with EO and EC. It may be concluded that soccer match induced fatigue increases the drop jump ground contact time, concomitant with the impairment of dynamic balance and agility performance when moving over a short distance. In contrast, there were no changes in the agility performance over a longer movement distance, explosive power of lower limbs, speed of step initiation, speed of the soccer kick, and static balance.